Ceftolozane/Tazobactam and Ceftazidime/Avibactam for Multidrug-Resistant Gram-Negative Infections in Immunocompetent Patients: A Single-Center Retrospective Study - Rosario Cultrera; Marco Libanore; Agostino Barozzi; Erica d'Anchera; Letizia Romanini; Fabio Fabbian; Francesco De Motoli; Brunella Quarta; Armando Stefanati; Niccolò Bolognesi; Giovanni Gabutti (MDPI AG, 2020)
Complicated infections from multidrug-resistant Gram-negative bacteria (MDR-GNB) represent a serious problem presenting many challenges. Resistance to many classes of antibiotics reduces the probability of an adequate empirical treatment, with unfavorable consequences, increasing morbidity and mortality. Readily available patient medical history and updated information about the local microbiological epidemiology remain critical for defining the baseline risk of MDR-GNB infections and guiding empirical treatment choices, with the aim of avoiding both undertreatment and overtreatment. There are few literature data that report real-life experiences in the use of ceftolozane/tazobactam and ceftazidime/avibactam, with particular reference to microbiological cure. Some studies reported experiences for the treatment of MDR-GNB infections in patients with hematological malignancies or specifically in Pseudomonas aeruginosa infections. We report our clinical single-center experience regarding the real-life use of ceftolozane/tazobactam and ceftazidime/avibactam to treat serious and complicated infections due to MDR-GNB and carbapenem-resistant Enterobacterales (CRE), with particular regard given to intra-abdominal and urinary tract infections and sepsis.